A biblioteca escolar no planejamento educacional: análise em escolas públicas de 10 e 2° graus em Recife-PE - Barros , Lucimar Martins de (1998)
It approaches the situation of the libraries in public schools of 1º and 2° degrees in Recife-PE, analyzing its real situation of functioning, physical installations, qualification of staff, documentations' availability, as well as its integration with the group of teachers, pedagogical-cultural activities and pupils. In view of that these libraries are considered element of great importance in the State Plans of Education, its conditions are jointly analyzed with the proposals of the government of improvement and bracket to the same ones, aiming at to compare the actions presented in the plans and the concretion of these actions. The study was carried through in 15 chosen schools as criteria determined in the methodology, in the city of Recife-PE, the period of March of 1995 the October of 1996. Questionnaires between responsable directors, pupils and responsables for libraries and from the gotten results had been applied, analysis of the proposals of the education plans was made and of it speaks of the three groups of actors of the research, mentioned above, being overcome as base the theoretical referencial, becoming prominence to the book " A miseria da biblioteca escolar ". The results gotten in the research disclose that the libraries in public schools of 1° and 2° degrees in Recife have suffered positive alterations, possessing personal trained and qualified to exert the function of regent of the library, as well as developed works didactic-pedagogical and cultural together with professors and route of the school. The concern of the governing is recognized, as for including the pertaining to school library in the educational planning, however some goals of improvements had still not been reached. Importance is evidenced it that these libraries have front to its public what it inside becomes essential its presence of the school, fact justified for the evidence of that they are instruments of pedagogical-cultural bracket in favor of education.